Effectiveness of training on de-escalation of violence and management of aggressive behavior faced by health care providers in a public sector hospital of Karachi - Baig, Lubna (Pak J Med Sci, 2018)
BACKGROUND & OBJECTIVE: Considering high burden of violence against healthcare workers in Pakistan APPNA Institute of Public Health developed a training to prevent reactive violence among healthcare providers. The purpose of this training was to equip healthcare providers with skills essential to control aggressive behaviors and prevent verbal and non-verbal violence in workplace settings. This study assesses the effectiveness of training in prevention, de-escalation and management of violence in healthcare settings. METHODS: A quasi-experimental study was conducted in October, 2016 using mixed method concurrent embedded design. The study assessed effectiveness of de-escalation trainings among health care providers working in emergency and gynecology and obstetrics departments of two teaching hospitals in Karachi. Quantitative assessment was done through structured interviews and qualitative through Focus Group Discussions. Healthcare providers` confidence in coping with patient aggression was also measured using a standard validated tool”. RESULTS: The overall self-perceived mean score of Confidence in Coping with Patient Aggression Instrument “(CCPAI)” scale was significantly higher in intervention group (Mean= 27.49, SD=3.53) as compared to control group (Mean= 23.92, SD=4.52) (p<0.001). No statistically significant difference was observed between intervention and control groups with regard to frequency of violence faced by HCPs post training and major perpetrators of violence.. CONCLUSION: De-escalation of violence training was effective in improving confidence of healthcare providers in coping with patient aggression.